Statistical Analysis of the Relationship Between Speed and Stopping Distance in Transportation Movements (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the statistical relationship between speed and stopping distance in transportation movements. The study aims to analyze how variations in vehicle speed influence the distance required to bring a vehicle to a complete stop. Using real-world data, various statistical methods, such as regression analysis, were applied to determine the strength and nature of the correlation. The findings suggest that the stopping distance increases significantly with speed, highlighting the importance of safe driving practices and road design in minimizing accidents. The results also provide valuable insights for transportation engineers and policymakers to optimize traffic safety measures.